Innate Allorecognition and Memory in Transplantation - Zhao, Daqiang; Abou-Daya, Khodor I.; Dai, Hehua; Oberbarnscheidt, Martin H.; Li, Xian C.; Lakkis, Fadi G. (Frontiers in Immunology, 2020)
Over the past few decades, we have witnessed a decline in the rates of acute rejection without significant improvement in chronic rejection. Current treatment strategies principally target the adaptive immune response and not the innate response. Therefore, better understanding of innate immunity in transplantation and how to target it is highly desirable. Here, we review the latest advances in innate immunity in transplantation focusing on the roles and mechanisms of innate allorecognition and memory in myeloid cells. These novel concepts could explain why alloimmune response do not abate over time and shed light on new molecular pathways that can be interrupted to prevent or treat chronic rejection.